Population structure and morphological sexual maturity of Achelous spinimanus (Latreille, 1819) (Decapoda, Portunoidea), a potential fishing resource in the southeastern coast of Brazil - De Sousa, Aline Nonato [UNESP]; Bernardes, Veronica Pereira [UNESP]; Da Silva, Thiago Elias [UNESP]; Bertini, Giovana [UNESP]; Taddei, Fabiano Gazzi [UNESP]; Fransozo, Adilson [UNESP] (My University, 2019)
This study brings some characteristics of a population of Achelous spinimanus in Ubatuba, northern coast of the State of São Paulo. The main aspects evaluated were sizefrequency distribution, sex ratio, and size at the onset of morphological sexual maturity. In total, 1,911 swimming crabs were captured, 502 juveniles (males and females), 350 adult males, 475 adult non-ovigerous females, and 584 ovigerous females. Males were larger (70.3 ± 18,2 mm) than females (66.2 ± 18.2 mm). The size CL at which 50% of the population is sexually mature was estimated 44.7 mm for males and 44.5 mm for females. The size-frequency distribution was polymodal for males and bimodal for females. This might suggest the occurrence of two or more age groups in the population probably due to the differential mortality and growth rates between males and females. Moreover, this study showed that the environmental conditions in Ubatuba were suitable for the establishment and growth of A. spinimanus during our surveys.
Keywords: Brachyura; Crustacea; Sex ratio; Size distribution; Ubatuba